Copper-based catalyst as well as preparation method and application thereof
The copper-based catalyst was prepared by a two-step precipitation method and the titanate coupling agent was introduced, which solved the problems of poor stability and low hydrogenation activity in the hydrogenation of carbon dioxide to methanol reaction, and achieved higher CO2 conversion and methanol yield.
Patent Information
- Application Number
- CN202411512538.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
AI Technical Summary
The existing copper-based catalysts have poor stability and low hydrogenation activity in the hydrogenation of carbon dioxide to methanol, resulting in low methanol yield.
The copper-based catalyst was prepared by a two-step precipitation method, and a hydrophobic titanate coupling agent was introduced in situ during the preparation process to improve the water resistance of the catalyst and the dispersion of active copper species.
It significantly improves CO2 conversion, methanol selectivity and methanol yield, while reducing catalyst deactivation.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysts, and in particular to a copper-based catalyst and a preparation method and application thereof. Background Art
[0002] In order to mitigate global warming caused by the increase in CO2 emissions, CO2 capture, utilization and storage (CCUS) technology has received increasing attention. In particular, the conversion of CO2 to produce high-value-added chemicals is considered an effective way to utilize CO2 resources. CO2 catalytic hydrogenation is the core method to achieve CO2 fixation and resource utilization. Methanol is an important chemical intermediate and a good vehicle fuel. Methanol production is mainly based on coal-to-methanol, but its carbon emission intensity is high, which is not conducive to carbon emission reduction. CO2 hydrogenation to methanol can not only effectively reduce the concentration of CO2 and alleviate the global greenhouse effect, but also provide a practical method for solving the energy crisis.
[0003] At present, the industrial catalyst for hydrogenation of carbon dioxide to methanol is copper-zinc-aluminum catalyst. Copper-based catalysts have excellent hydrogenation activity compared to other catalysts. However, due to the low Tammann temperature of the copper species in the active center of copper-based catalysts, the catalyst is prone to sintering under high temperature conditions, and water will be generated during the reaction, which will accelerate the sintering of the catalyst and the oxidation of the active Cu species, leading to the deactivation of the catalyst. Therefore, constructing a stable copper-based catalyst is the key to improving catalyst performance.
[0004] The poor stability and low hydrogenation activity of copper-based catalysts during the reaction are key technical issues that need to be solved in the hydrogenation of carbon dioxide to methanol. During the process of hydrogenation of carbon dioxide to methanol, water is produced, which oxidizes Cu to Cu with poor activity. 2+ , and accelerate the sintering of copper species to deactivate the catalyst. The active copper species of copper-based catalysts have a low Tamman temperature, and copper species are prone to sintering, resulting in catalyst deactivation. In addition, due to the uneven particle size of the prepared copper catalyst, the catalyst will undergo Ostwald ripening, resulting in the growth of copper particles. Affected by thermodynamic equilibrium limitations, the equilibrium conversion rate of carbon dioxide hydrogenation to methanol is low. On this basis, the intrinsic activity of the active centers of existing catalysts is insufficient, which leads to a low methanol yield of the catalyst. Summary of the invention
[0005] In view of this, the present invention is committed to providing a copper-based catalyst and a preparation method and application thereof, so as to solve the problem of low methanol yield in the carbon dioxide hydrogenation to methanol reaction due to insufficient intrinsic activity of the catalyst active center in the prior art.
[0006] In order to solve the above technical problems, this application is implemented as follows:
[0007] A first aspect of the present invention provides a method for preparing a copper-based catalyst, the preparation method comprising the following steps:
[0008] S1, mixing a first solution containing a zinc source and an aluminum source with an alkaline precipitant solution to obtain a suspension; mixing the suspension, a second solution containing a copper source and the alkaline precipitant solution to obtain a mixed material;
[0009] S2, subjecting the mixed material to an aging treatment to obtain an aged slurry;
[0010] S3, washing the aged slurry, drying it and calcining it;
[0011] The second solution further contains a coupling agent and a metal auxiliary agent; the coupling agent includes a titanate coupling agent; the metal auxiliary agent contains a first metal element, and the first metal element is selected from at least one of the elements of Group IIA, Group IVB and Group VIB.
[0012] Optionally, the titanate coupling agent includes at least one of di(dioctyl pyrophosphate)ethylene glycol titanate, isopropyl tri(dioctyl pyrophosphate) titanate and di(octyl pyrophosphate)hydroxyacetic acid titanate; based on the mass of the copper-based catalyst, the content of TiO2 contained in the titanate coupling agent is 1 to 5 wt.%.
[0013] Optionally, the first metal element is selected from at least one of zirconium, chromium, magnesium, calcium and strontium; the metal additive comprises a soluble salt of the first metal element; and the content of the metal additive is 0.5-3wt.% based on the mass of the copper-based catalyst.
[0014] Optionally, the alkaline precipitant contained in the alkaline precipitant solution includes at least one of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate; in the alkaline precipitant solution, the concentration of the alkaline precipitant is 0.5 to 2.0 mol / L.
[0015] Optionally, the copper source is calculated as Cu content, the zinc source is calculated as ZnO, and the aluminum source is calculated as Al2O3, and the mass ratio of the copper source, the zinc source and the aluminum source contained in the mixed material is (5-7): (2-3): (1-2).
[0016] Optionally, the zinc source is a soluble salt of zinc; optionally, the zinc source includes at least one of zinc acetate, zinc sulfate and zinc chloride; the aluminum source is a soluble salt of aluminum; optionally, the aluminum source includes at least one of aluminum acetate, aluminum sulfate and aluminum chloride; the copper source is a soluble salt of copper; optionally, the copper source includes at least one of copper acetate, copper sulfate and copper chloride.
[0017] Optionally, in step S1, the pH of the system during the first mixing process is not less than 7, and the pH of the system during the second mixing process is not less than 7; in step S2, the conditions for the aging treatment include: a temperature of 50 to 70°C and a time of 2 to 20 hours; in step S3, the conditions for the drying treatment include: a temperature of 100 to 120°C and a time of 8 to 12 hours; the conditions for the calcination treatment include: a temperature of 300 to 500°C and a time of 3 to 5 hours.
[0018] The second aspect of the present invention provides a copper-based catalyst prepared according to the above method.
[0019] The third aspect of the present invention provides a method for preparing methanol by hydrogenating carbon dioxide, the method comprising: passing a reaction gas into a reactor filled with a catalyst to carry out a reaction of preparing methanol by hydrogenating carbon dioxide;
[0020] Wherein, the catalyst includes the copper-based catalyst prepared according to the above method and / or the above copper-based catalyst.
[0021] Optionally, the reaction gas includes H2 and CO2; the volume ratio of H2 to CO2 in the reaction gas is 1 to 5:1; the conditions for the carbon dioxide hydrogenation reaction to produce methanol include: pressure 3.0 to 7.0 MPa, temperature 200 to 400°C, gas space velocity 5000 to 15000 h -1 .
[0022] Through the above technical solution, the beneficial technical effects of the present invention are:
[0023] (1) The present invention introduces hydrophobic titanate in situ during the preparation of the copper-based catalyst. On the one hand, it can construct a hydrophobic interface on the catalyst surface, improve the water resistance of the catalyst, and effectively inhibit the oxidation and sintering of active species induced by water, thereby reducing the deactivation of the catalyst; on the other hand, it can improve the dispersion of active copper species in the copper-based catalyst, effectively inhibit Oswald ripening caused by uneven copper particles in the catalyst, thereby reducing the deactivation of the catalyst. In addition, the introduction of titanate is also beneficial to improving the dispersion of active copper species and the hydrogenation activity of the catalyst.
[0024] (2) The copper-based catalyst prepared by the present invention is applied to the reaction of hydrogenating carbon dioxide to produce methanol, which can significantly improve the CO2 conversion rate, methanol selectivity and methanol yield.
[0025] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0026] The present invention discloses a copper-based catalyst and a preparation method and application thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the above. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0027] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0032] In order to solve the problem of low methanol yield in the reaction of hydrogenating carbon dioxide to methanol due to insufficient intrinsic activity of the catalyst active center in the prior art, the present invention adopts the following technical solution:
[0033] A first aspect of the present invention provides a method for preparing a copper-based catalyst, the preparation method comprising the following steps:
[0034] S1, mixing a first solution containing a zinc source and an aluminum source with an alkaline precipitant solution to obtain a suspension; mixing the suspension, a second solution containing a copper source and the alkaline precipitant solution to obtain a mixed material;
[0035] S2, subjecting the mixed material to an aging treatment to obtain an aged slurry;
[0036] S3, washing the aged slurry, drying it and calcining it;
[0037] The second solution further contains a coupling agent and a metal auxiliary agent; the coupling agent includes a titanate coupling agent; the metal auxiliary agent contains a first metal element, and the first metal element is selected from at least one of the elements of Group IIA, Group IVB and Group VIB.
[0038] The present invention adopts a two-step precipitation method to prepare a copper-based catalyst, specifically, firstly, a first solution containing a zinc source and an aluminum source is mixed with an alkaline precipitant solution to precipitate Zn and Al to synthesize a Zn / Al hydrotalcite structure; and then a suspension containing Zn and Al, a second solution containing a copper source and an alkaline precipitant solution are mixed for a second time to precipitate the first metal element Cu. The preparation of the copper-based catalyst by the two-step precipitation method is more conducive to exposing more Cu active sites.
[0039] According to the present invention, in the process of preparing the copper-based catalyst, a hydrophobic titanate is introduced in situ. On the one hand, a hydrophobic interface can be constructed on the surface of the catalyst, the water resistance of the catalyst can be improved, and the oxidation and sintering of the active species induced by water can be effectively inhibited, thereby reducing the deactivation of the catalyst; on the other hand, the dispersion of the active copper species in the copper-based catalyst can be improved, and the Oswald ripening caused by the uneven copper particles in the catalyst can be effectively inhibited, thereby reducing the deactivation of the catalyst. In addition, the introduction of titanate is also beneficial to improve the dispersion of active species copper and the hydrogenation activity of the catalyst. The titanate coupling agent in the present invention can include at least one of di(dioctyl pyrophosphate acyloxy) ethylene glycol titanate (NDZ-311), isopropyl tri(dioctyl pyrophosphate acyloxy) titanate (NDZ-201) and di(octyl pyrophosphate) glycol titanate (KR-138S). In the present invention, based on the mass of the copper-based catalyst, the content of TiO2 contained in the titanate coupling agent is 1 to 5wt.%.
[0040] According to the present invention, in the process of preparing the catalyst, adding a metal additive can improve the dispersion of the active species Cu of the catalyst, which is beneficial to improving the hydrogenation activity of the catalyst, and can inhibit the sintering of the Cu species during the reaction. At the same time, some hydrophobic additives are beneficial to improving the surface hydrophobicity of the catalyst, thereby inhibiting the oxidation and sintering of Cu caused by the presence of water vapor. The first metal element in the present invention can be selected from at least one of zirconium, chromium, magnesium, calcium and strontium; the metal additive can include a soluble salt of the first metal element; illustratively, the metal additive can be a nitrate of the first metal element. In the present invention, based on the mass of the copper-based catalyst, the content of the metal additive is 0.5-3wt.%.
[0041] According to the present invention, the alkaline precipitant contained in the alkaline precipitant solution may include at least one of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate; in the alkaline precipitant solution, the concentration of the alkaline precipitant may be 0.5 to 2.0 mol / L. In an embodiment of the present invention, the alkaline precipitant is added in two steps, and the proportion of the alkaline precipitant added in the first mixing step and the second mixing step can be adjusted according to actual conditions, and no further restrictions are made here.
[0042] According to the present invention, the copper source is calculated as Cu content, the zinc source is calculated as ZnO, and the aluminum source is calculated as Al2O3. The mass ratio of the copper source, the zinc source and the aluminum source contained in the mixed material can be (5-7): (2-3): (1-2).
[0043] According to the present invention, the zinc source may be a soluble salt of zinc; exemplarily, the zinc source includes at least one of zinc acetate, zinc sulfate and zinc chloride; the aluminum source may be a soluble salt of aluminum; exemplarily, the aluminum source includes at least one of aluminum acetate, aluminum sulfate and aluminum chloride; the copper source may be a soluble salt of copper; exemplarily, the copper source includes at least one of copper acetate, copper sulfate and copper chloride.
[0044] According to the present invention, in step S1, the pH value of the system in the first mixing process is preferably not less than 7, and the pH value of the system in the second mixing process is preferably not less than 7; in step S2, the conditions for the aging treatment may include: a temperature of 50 to 70°C and a time of 2 to 20 hours; in step S3, the conditions for the drying treatment may include: a temperature of 100 to 120°C and a time of 8 to 12 hours; the conditions for the roasting treatment may include: a temperature of 300 to 500°C and a time of 3 to 5 hours.
[0045] In a specific embodiment of the present invention, the step of "mixing the suspension, the second solution containing the copper source and the alkaline precipitant solution for a second time to obtain a mixed material" involved in step S1 may include: dripping / mixing the second solution containing the copper source and the alkaline precipitant into the suspension to form a mixed material.
[0046] The preparation method of the present invention may also include: mixing a zinc source, an aluminum source and water to obtain a first solution; mixing a copper source, a metal auxiliary agent, a coupling agent and water to obtain a second solution; and mixing an alkaline precipitant with water to obtain an alkaline precipitant solution.
[0047] The second aspect of the present invention provides a copper-based catalyst prepared according to the above method.
[0048] According to the present invention, the mass ratio of copper, zinc oxide and aluminum oxide contained in the copper-based catalyst may be (5-7): (2-3): (1-2).
[0049] The copper-based catalyst provided by the present invention further contains an oxide of a first metal and a titanate coupling agent. Based on the total mass of the copper-based catalyst, the content of the oxide of the first metal may be 0.5-3wt%, and the content of the titanate coupling agent may be 2-5wt%.
[0050] The third aspect of the present invention provides a method for producing methanol by hydrogenating carbon dioxide, the method comprising: passing the reaction gas into a reactor filled with a catalyst to carry out a carbon dioxide hydrogenation to produce methanol reaction; wherein the catalyst comprises a copper-based catalyst prepared according to the above method and / or the above-mentioned copper-based catalyst.
[0051] According to the present invention, the reaction gas may include H2 and CO2; the volume ratio of H2 to CO2 in the reaction gas may be 1 to 5:1; the conditions for the carbon dioxide hydrogenation reaction to produce methanol may include: pressure 3.0 to 7.0 MPa, temperature 200 to 400°C, gas space velocity 5000 to 15000 h -1 .
[0052] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0053] Example 1
[0054] The mass ratio of Cu / ZnO / Al2O3 in the catalyst of this embodiment is 5:3:1, and ZrO2 and TiO2 in NDZ-311 account for 1wt% and 2wt% of the total mass of the catalyst, respectively.
[0055] The specific preparation method of the catalyst of this embodiment is as follows:
[0056] Weigh 9.02g zinc nitrate hexahydrate and 6.34g aluminum nitrate nonahydrate, add 98mL deionized water, stir and dissolve in a 500mL beaker to obtain a first solution; weigh 16.37g copper nitrate trihydrate, 0.38g zirconium nitrate and 1.5g NDZ-311 and dissolve in 137mL deionized water to obtain a second solution. Weigh 41.6g anhydrous sodium carbonate, add 400mL deionized water, stir and dissolve to form a 1mol / L precipitant solution.
[0057] First, the first solution and the precipitant solution were simultaneously added dropwise to a three-necked flask containing 100 mL of deionized water, and the pH value of the system in the three-necked flask was maintained at 7. After the first solution was added dropwise, a suspension was obtained; the second solution and the precipitant solution were added dropwise to the above suspension, and the pH value in the system was maintained at 7. After the addition was completed, a mixed material was obtained. The mixed material was aged at 60°C for 12 hours to obtain an aged slurry; the aged slurry was washed and dried and calcined to obtain a sample Cat.1 catalyst, wherein the drying temperature was 110°C and the time was 10 hours; the calcination was carried out in a muffle furnace at a temperature of 300°C and a time of 4 hours.
[0058] Example 2
[0059] The mass ratio of Cu / ZnO / Al2O3 in the catalyst of this embodiment is 5:3:2, and Cr2O3 and TiO2 in NDZ-311 account for 2wt.% and 4wt.% of the total mass of the catalyst respectively.
[0060] The specific preparation method of the catalyst of this embodiment is as follows:
[0061] Weigh 8.04g zinc nitrate hexahydrate and 11.29g aluminum nitrate nonahydrate, add 196mL deionized water, stir and dissolve in a 500mL beaker to obtain a first solution; weigh 14.58g copper nitrate trihydrate, 0.31g chromium nitrate and 3.0g NDZ-311 and dissolve in 203mL deionized water to obtain a second solution. Weigh 41.6g anhydrous sodium carbonate, add 400mL deionized water, stir and dissolve to form a 1mol / L precipitant solution.
[0062] First, the first solution and the precipitant solution were simultaneously added dropwise to a three-necked flask containing 100 mL of deionized water, and the pH value of the system in the three-necked flask was maintained at 7.5. After the first solution was added dropwise, a suspension was obtained; the second solution and the precipitant solution were added dropwise to the above suspension, and the pH in the system was maintained at 7.5 to obtain a mixed material. The suspension was maintained at 70°C for 8 hours to obtain an aged slurry; the aged slurry was washed and dried and calcined to obtain a sample Cat.2 catalyst, wherein the drying temperature was 110°C and the time was 10 hours; the calcination was carried out in a muffle furnace at a temperature of 350°C and a time of 4 hours.
[0063] Example 3
[0064] The mass ratio of Cu / ZnO / Al2O3 in the catalyst of this embodiment is 4:3:2, and MgO and TiO2 in NDZ-201 account for 3wt.% and 3wt.% of the total mass of the catalyst respectively.
[0065] The specific method of the catalyst of this embodiment is as follows:
[0066] Weigh 8.74g zinc nitrate hexahydrate and 12.29g aluminum nitrate nonahydrate, add 214mL deionized water, stir and dissolve in a 500mL beaker to obtain a first solution; weigh 12.69g copper nitrate trihydrate, 1.53g magnesium nitrate and 3.93g NDZ-201 and dissolve in 194mL deionized water to obtain a second solution. Weigh 41.6g anhydrous sodium carbonate, add 400mL deionized water, stir and dissolve to form a 1mol / L precipitant solution.
[0067] First, the first solution and the precipitant solution were simultaneously added dropwise to a three-necked flask containing 100 mL of deionized water, and the pH value of the system in the three-necked flask was maintained at 8. After the first solution was added dropwise, a suspension was obtained; the second solution and the precipitant solution were added dropwise to the above suspension, and the pH value in the system was maintained at 8. After the addition was completed, a mixed material was obtained. The mixed material was maintained at 50°C for 4 hours to obtain an aged slurry; the aged slurry was washed and dried and calcined to obtain a sample Cat.3 catalyst, wherein the drying temperature was 110°C and the time was 10 hours; the calcination was carried out in a muffle furnace at a temperature of 450°C and a time of 4 hours.
[0068] Example 4
[0069] The mass ratio of Cu / ZnO / Al2O3 in the catalyst of this embodiment is 6:3:1, and TiO2 in SrO and NDZ-201 accounts for 2wt.% and 3wt.% of the total mass of the catalyst respectively.
[0070] The specific preparation method of the catalyst of this embodiment is as follows:
[0071] Weigh 7.95g zinc nitrate hexahydrate and 5.59g aluminum nitrate nonahydrate, add 145mL deionized water, stir and dissolve in a 500mL beaker to obtain a first solution; weigh 17.31g copper nitrate trihydrate, 0.33g strontium nitrate and 3.93g NDZ-201 and dissolve in 243mL deionized water to obtain a second solution. Weigh 41.6g anhydrous sodium carbonate, add 400mL deionized water, stir and dissolve to form a 1mol / L precipitant solution.
[0072] First, the first solution and the precipitant solution were simultaneously added dropwise to a three-necked flask containing 100 mL of deionized water, and the pH value of the system in the three-necked flask was maintained at 9. After the first solution was added dropwise, a suspension was obtained; the second solution and the precipitant solution were added dropwise to the above suspension, and the pH value in the system was maintained at 9. After the addition was completed, a mixed material was obtained. The mixed material was maintained at 70°C for 16 hours to obtain an aged slurry; the aged slurry was washed and dried and calcined to obtain a sample Cat.4 catalyst, wherein the drying temperature was 110°C and the time was 10 hours; the calcination was carried out in a muffle furnace at a temperature of 500°C and a time of 4 hours.
[0073] Example 5
[0074] The mass ratio of Cu / ZnO / Al2O3 in the catalyst of this embodiment is 56:33:11, and the CaO additive and TiO2 in KR-138S account for 1wt.% and 2wt.% of the total mass of the catalyst respectively.
[0075] The specific preparation method of the catalyst of this embodiment is as follows:
[0076] Weigh 8.93g zinc nitrate hexahydrate and 6.28g aluminum nitrate nonahydrate, add 163mL deionized water, stir and dissolve in a 500mL beaker to obtain a first solution; weigh 16.50g copper nitrate trihydrate, 0.14g calcium nitrate and 2.0g KR-138S and dissolve in 228mL deionized water to obtain a second solution. Weigh 41.6g anhydrous sodium carbonate, add 400mL deionized water, stir and dissolve to form a 1mol / L precipitant solution.
[0077] First, the first solution and the precipitant solution were simultaneously added dropwise to a three-necked flask containing 100 mL of deionized water, and the pH value of the system in the three-necked flask was maintained at 8.5. After the first solution was added dropwise, a suspension was obtained; the second solution and the precipitant solution were added dropwise to the suspension, and the pH value in the system was maintained at 8.5. After the addition was completed, a mixed material was obtained. The mixed material was aged at 60°C for 2 hours to obtain an aged slurry; the aged slurry was washed and dried and calcined to obtain a sample Cat.5 catalyst, wherein the drying temperature was 110°C and the time was 10 hours; the calcination was carried out in a muffle furnace at a temperature of 350°C and a time of 4 hours.
[0078] Example 6
[0079] The mass ratio of Cu / ZnO / Al2O3 in the catalyst of this embodiment is 60:25:15, and ZrO2 and TiO2 in KR-138S account for 3wt.% and 5wt.% of the total mass of the catalyst respectively.
[0080] The specific preparation method of the catalyst of this embodiment is as follows:
[0081] Weigh 6.42g zinc nitrate hexahydrate and 8.12g aluminum nitrate nonahydrate, add 149mL deionized water, stir and dissolve in a 500mL beaker to obtain a first solution; weigh 16.77g copper nitrate trihydrate, 1.14g zirconium nitrate and 5.0g KR-138S and dissolve in 244mL deionized water to obtain a second solution. Weigh 41.6g anhydrous sodium carbonate, add 400mL deionized water, stir and dissolve to form a 1mol / L precipitant solution.
[0082] First, the first solution and the precipitant solution were simultaneously added dropwise to a three-necked flask containing 100 mL of deionized water, and the pH value of the system in the three-necked flask was maintained at 9. After the first solution was added dropwise, a suspension was obtained; the second solution and the precipitant solution were added dropwise to the suspension, and the pH value in the system was maintained at 9, and a mixed material was obtained after the addition was completed. The mixed material was maintained at 70°C for 16 hours to obtain an aged slurry; the aged slurry was washed and dried and calcined to obtain a sample Cat.6 catalyst, wherein the drying temperature was 110°C and the time was 10 hours; the calcination was carried out in a muffle furnace at a temperature of 450°C and a time of 4 hours.
[0083] Comparative Example 1
[0084] The mass ratio of Cu / ZnO / Al2O3 in the catalyst in this comparative example is 6:3:1, and no other additives are added.
[0085] The specific preparation method of the catalyst of this comparative example is as follows:
[0086] Weigh 8.37g zinc nitrate hexahydrate and 5.88g aluminum nitrate nonahydrate, add 152mL deionized water, stir and dissolve in a 500mL beaker to obtain a first solution; weigh 18.23g copper nitrate trihydrate and dissolve in 250mL deionized water to obtain a second solution. Weigh 41.6g anhydrous sodium carbonate, add 400mL deionized water, stir and dissolve to form a 1mol / L precipitant solution.
[0087] First, the first solution and the precipitant solution were simultaneously added dropwise to a three-necked flask containing 100 mL of deionized water, and the pH value of the system in the three-necked flask was maintained at 8. After the first solution was added dropwise, a suspension was obtained; the second solution and the precipitant solution were added dropwise to the suspension, and the pH value in the system was maintained at 8. After the addition was completed, a mixed material was obtained. The mixed material was aged at 70°C for 8 hours to obtain an aged slurry; the aged slurry was washed and dried and calcined to obtain a sample Cat.7 catalyst, wherein the drying temperature was 110°C and the time was 10 hours; the calcination was carried out in a muffle furnace at a temperature of 500°C and a time of 4 hours.
[0088] Test Example 1
[0089] The catalysts prepared in Examples 1 to 6 and Comparative Example 1 were respectively applied to the carbon dioxide hydrogenation to methanol reaction for testing, and the test results are shown in Table 1. The carbon dioxide hydrogenation to methanol reaction conditions include: reaction temperature of 250°C, reaction pressure of 5 MPa, reaction space velocity of 10000 mL·h -1 ·g cat -1 , the flow ratio of H2 and CO2 is 3:1.
[0090] Table 1
[0091]
[0092] It can be seen from the data in Table 1 that the catalyst prepared in the embodiment of the present invention has a higher CO2 conversion rate, methanol selectivity and methanol yield in the reaction of carbon dioxide hydrogenation to methanol, while having a lower deactivation rate.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a copper-based catalyst, characterized in that: The preparation method comprises the following steps: S1, mixing a first solution containing a zinc source and an aluminum source with an alkaline precipitant solution to obtain a suspension; mixing the suspension, a second solution containing a copper source and the alkaline precipitant solution to obtain a mixed material; S2, subjecting the mixed material to an aging treatment to obtain an aged slurry; S3, washing the aged slurry, drying it and calcining it; The second solution further contains a coupling agent and a metal auxiliary agent; the coupling agent includes a titanate coupling agent; the metal auxiliary agent contains a first metal element, and the first metal element is selected from at least one of the elements of Group IIA, Group IVB and Group VIB.
2. The preparation method according to claim 1, characterized in that: The titanate coupling agent includes at least one of di(dioctyl pyrophosphate acyloxy)ethylene glycol titanate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and di(octyl pyrophosphate) glycolate titanate; Based on the mass of the copper-based catalyst, the content of TiO2 in the titanate coupling agent is 1 to 5 wt.%.
3. The preparation method according to claim 1, characterized in that: The first metal element is selected from at least one of zirconium, chromium, magnesium, calcium and strontium; The metal additive includes a soluble salt of the first metal element; Based on the mass of the copper-based catalyst, the content of the metal additive is 0.5-3wt.%.
4. The preparation method according to claim 1, characterized in that: The alkaline precipitant solution contains an alkaline precipitant including at least one of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate; In the alkaline precipitant solution, the concentration of the alkaline precipitant is 0.5-2.0 mol / L.
5. The preparation method according to claim 1, characterized in that: The copper source is calculated as Cu content, the zinc source is calculated as ZnO, and the aluminum source is calculated as Al2O3. The mass ratio of the copper source, the zinc source and the aluminum source contained in the mixed material is (5-7): (2-3): (1-2).
6. The preparation method according to claim 1 or 5, characterized in that: The zinc source is a soluble salt of zinc; optionally, the zinc source includes at least one of zinc acetate, zinc sulfate and zinc chloride; The aluminum source is a soluble salt of aluminum; optionally, the aluminum source includes at least one of aluminum acetate, aluminum sulfate and aluminum chloride; The copper source is a soluble salt of copper; optionally, the copper source includes at least one of copper acetate, copper sulfate and copper chloride.
7. The preparation method according to claim 1, characterized in that: In step S1, the pH of the system during the first mixing process is not less than 7, and the pH of the system during the second mixing process is not less than 7; In step S2, the aging treatment conditions include: temperature of 50 to 70°C and time of 2 to 20 hours; In step S3, the conditions for the drying treatment include: a temperature of 100-120° C. and a time of 8-12 hours; the conditions for the calcination treatment include: a temperature of 300-500° C. and a time of 3-5 hours.
8. A copper-based catalyst prepared according to the method according to any one of claims 1 to 7.
9. A method for preparing methanol by hydrogenating carbon dioxide, characterized in that: The method comprises: introducing a reaction gas into a reactor filled with a catalyst to carry out a carbon dioxide hydrogenation to methanol reaction; Wherein, the catalyst comprises the copper-based catalyst prepared by the preparation method according to claims 1 to 7 and / or the copper-based catalyst according to claim 8.
10. The method according to claim 9, characterized in that The reaction gas includes H2 and CO2; the volume ratio of H2 to CO2 in the reaction gas is 1 to 5:1; The conditions for the carbon dioxide hydrogenation to methanol reaction include: pressure 3.0-7.0 MPa, temperature 200-400° C., gas space velocity 5000-15000 h -1 .
Citation Information
Cited By
Graphite-modified catalyst for methanol synthesis from mixed gas and method for preparing the same
CN122625213A